19 varsities make it to 'excellent' - New Straits Times , Farrah Naz Karim (2010)
Not a single institution of higher learning in the country, including Universiti Sains Malaysia (USM), which was granted apex status the year before, was rated "outstanding" in the 2009 Rating System for Institutions of Higher Learning (Setara).